S-adenosylmethionine treatment affects histone methylation in prostate cancer cells - Mathes, Arthur; Duman, Merve Busra; Neumann, Alexander; Dobreva, Gergana; Schmidt, Thomas (Gene, 2024)
S-adenosylmethionine (SAM) represents a potent inhibitor of cancer cell proliferation, migration, and invasionin vitro.The underlying mechanisms remain elusive. Here, we examined, if treatment with SAM may cause alterations in the methylation of the histone marks H3K4me3 and H3K27me3, which are both known to play important roles in the initiation and progression of prostate cancer. We treated PC-3 cells with 200 µmol SAM, a concentration known to cause anticancerogenic effects, followed by ChIP-sequencing for H3K4me3 and H3K27me3. We detected 236 differentially methylated regions for H3K27me3 and 560 differentially methylated regions for H3K4me3. GO Term enrichment showed upregulation of anticancerogenic, as well as downregulation of cancerogenic related biological processes, molecular functions, and pathways. Furthermore, we compared specific methylation profiles of SAM treated samples to gene expression changes (RNA-Seq). 35 upregulated and 56 downregulated genes (total: 604 differentially expressed genes) could be related to hypomethylated and hypermethylated regions. 17 upregulated genes could be identified as tumor suppressor genes, 45 downregulated genes in contrast are considered as oncogenes. As a conclusion it can be stated that SAM treatment of prostate cancer cells resulted in alterations of H3K4me3 and H3K27me3 methylation profiles. Gene to peak annotation, alignment with results of a transcriptome study as well as GO-term analysis underpinned the biological relevance of methylation changes.